Novel Tetrazoles against Acanthamoeba Castellanii belonging to the T4 genotype - Yassmin, Isse Wehelie *; Khan, Naveed Ahmed; Fatima, Itrat; Anwar, Areeba; Kanwal, Kanwal; Khan, Khalid Mohammed; Siddiqui, Ruqaiyyah; Tong, Tommy Yuh Koon *; Ayaz, Anwar * (S. Karger AG, 2021)
Background: Acanthamoeba castellanii is a pathogenic freeliving amoeba responsible for blinding keratitis and fatal granulomatous amoebic encephalitis. However, treatments are not standardized but can involve the use of amidines, biguanides, and azoles. Objectives: The aim of this study was to synthesize a variety of synthetic tetrazole derivatives and test their activities against A. castellanii. Methods: A series of novel tetrazole compounds were synthesized by one-pot method and characterized by NMR and mass spectroscopy. These compounds were subjected to amoebicidal and cytotoxicity assays against A. castellanii belonging to the T4 genotype and human keratinocyte skin cells, respectively. Additionally, reactive oxygen species determination and electron microscopy studies were carried out. Furthermore, two of the seven compounds were conjugated with silver nanoparticles to study their anti-amoebic potential. Results: A series of seven tetrazole derivatives were synthesized successfully. The selected tetrazoles showed anti-amoebic activities at 10 μM concentration against A. castellanii in vitro. The compounds tested caused increased reactive oxygen species generation in A. castellanii and morphological damage to amoebal membranes. Moreover, conjugation of silver nanoparticles enhanced anti-amoebic effects of two tetrazoles. Conclusions: The results showed that azole compounds hold promise in the development of new formulations of anti-Acanthamoebic agents. © 2021 S. Karger AG, Basel.